MULTIFUNCTIONAL Ni-Cr-Al-Y COATINGS VIA THERMAL SPRAYING - Roata, Ionut Claudiu; Plamadiala Ioan; Uncu Ionut (Acta Technica Napocensis, 2023)
This paper explores the thermal spraying of Ni-Cr-Al-Y coatings via the flame spraying technique. Our study addresses a critical knowledge gap by offering precise microstructural control, resulting in a good reduction in porosity compared to existing literature. We demonstrate superior corrosion resistance with a 90 % reduction in corrosion rate in a 3.5 % wt. aqueous NaCl solution. Moreover, our coatings exhibit a highly hydrophilic nature with a contact angle of 16-30 degrees, making them promising for humid environments. We emphasize the sustainable and cost-effective advantages of flame spraying, showcasing its potential for large-scale production. Overall, our research significantly advances the understanding of multifunctional coatings and their practical applications.
Keywords: thermal spraying; corrosion resistance; microstructure; surface properties; coatings